Augmented Reality as Potential Learning Media For Early Children Education - Haula Millati Azka; Lara Fridani; Tjipto Sumadi (Universitas Panca Sakti Bekasi, 2024)
Learning media is an important learning tool for teachers, especially early childhood teachers. Early childhood has a limited period of focus, therefore, in providing stimulation to early childhood, learning media is needed to create an interesting, active and fun atmosphere. This research is motivated by teachers' limitations in using innovative learning media, such as through pictures and posters. The use of learning media such as technology is still rarely used in learning. The aim of this research is to determine the potential in using learning media. The method used in this research is a qualitative descriptive research method with literature study. The subjects of this research were kindergarten teachers in the Banana area, East Jakarta. In this research, researchers used written sources such as articles, journals and relevant documents in studying this topic. The results of research from this literature study are that Augmented Reality has the potential to increase attraction and interest in learning, create an interactive learning atmosphere, and make it easier for children to imagine in concrete form